2012
DOI: 10.1155/2012/135387
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multilabel Learning Using the Relevant Feature for Each Label in Chronic Gastritis Syndrome Diagnosis

Abstract: Background. In Traditional Chinese Medicine (TCM), most of the algorithms are used to solve problems of syndrome diagnosis that only focus on one syndrome, that is, single label learning. However, in clinical practice, patients may simultaneously have more than one syndrome, which has its own symptoms (signs). Methods. We employed a multilabel learning using the relevant feature for each label (REAL) algorithm to construct a syndrome diagnostic model for chronic gastritis (CG) in TCM. REAL combines feature sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
(7 reference statements)
0
17
0
Order By: Relevance
“…This behavior could be partly explained by the relative lower computational cost in comparison with other alternatives. In addition, these strategies can be combined, as exemplified by IG-BR and some proposals from the related work [34][35][36][37]5]. In particular, these filter methods apply the Information Gain importance measure in binary data directly or indirectly transformed by the BR approach, a first-order strategy.…”
Section: Related Work Found By the Systematic Review Methodsmentioning
confidence: 99%
“…This behavior could be partly explained by the relative lower computational cost in comparison with other alternatives. In addition, these strategies can be combined, as exemplified by IG-BR and some proposals from the related work [34][35][36][37]5]. In particular, these filter methods apply the Information Gain importance measure in binary data directly or indirectly transformed by the BR approach, a first-order strategy.…”
Section: Related Work Found By the Systematic Review Methodsmentioning
confidence: 99%
“…The task of multi-label learning (or multi-label classification) is to learn a function h : χ → 2 y that maps each instance x ∈ χ into a set of proper labels h ( x )⊆ y [25]. REAL, a new multi-label leaning algorithm with features selected through the maximization of mutual information, was proposed by our research team and was confirmed suitable for TCM Zheng differentiation [13, 26]. For this method, feature variables associated mostly with Zheng were selected according to maximization of mutual information.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, TCM Zheng patterns can be classified as a multi-label problem that traditional single-label learning algorithms cannot solve. The multi-label learning (MLL) algorithm REAL is suitable for solving multi-label recognition of TCM Zheng patterns [13]. This algorithm was applied to construct Zheng classification models based on different datasets.…”
Section: Introductionmentioning
confidence: 99%
“…TCM state identification is researched for the relationships of symptoms, syndromes and locations and natures of diseases, which is complex and ambiguous. TCM state identification can be applied in the study of various diseases in Western Medicine, such as coronary heart disease (CHD), Chronic gastritis (CG), and lupus erythematosus . TCM state identification expounds the objective and obscure relationships of symptoms, syndromes, and locations and natures of diseases by considering all things as a whole and correlating with each other.…”
Section: Introductionmentioning
confidence: 99%